Information experiments - Ingar Haaland; Julian König; Christopher Roth; Johannes Wohlfart (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
Information provision experiments have become pivotal in understanding how beliefs influence human behavior in various social science contexts. These experiments, which manipulate the information sets available to respondents, enable the exogenous alteration of beliefs and perceived constraints, providing valuable insights. This review article explores methodologies for measuring and updating beliefs, designing effective information treatments, and addressing experimenter demand effects. The paper also discusses the challenges of belief measurement, such as overcoming numerical anchoring and understanding the persistence of belief changes. Additionally, it highlights the growing importance of studying the impact of qualitative information and the attentional foundations of expectation formation.
Keywords: C90; D83; 330; Information